The institution of neoliberal rationality in Brazilian educational policies based on the “keep learning” and “learn to learn” principles - Audrei Rodrigo da Conceição Pizolati (Education Policy Analysis Archives, 2021)
Considering the current neoliberal context and its implications in the field of education, the objective is to examine the discursive genesis of the “learn to learn” principle that privileges “continue learning”, pointed out by educational policies for high school. For this, based on theoretical and methodological bases in the studies of Educational Policies and Curriculum, a historical-documental analysis is carried out. The materiality chosen concerns the legal frameworks that followed the National Law of Guidelines and Bases of Education (LDBEN, 1996). It is observed that the constitution of the neosubject, in a flexible, responsible and autonomous way, resides in the promulgation of LDBEN and is gradually supported in the educational and curricular policies that underlie the Common National Curriculum Base-High School. The meaning assumed by Brazilian education today is in line with what the market proclaims, in which it is intended to internalize and value assumptions such as entrepreneurship and self-entrepreneurship. Thus, neoliberal rationality tends to consolidate itself through the individuation and flexible autonomy of the formative itinerary aimed at high school. In this process, the institution of neosubjects throughout life is encouraged.